Supervised internship in Health Psychology during a COVID-19 pandemic (Research, Society and Development, 2020)
Health psychology has the responsibility to provide the subject with autonomy in relation to the care of their health. With this, it is verified the relevance of psychology in the construction of health promotion actions as in waiting room actions. The mandatory internship is a very important step for students. Because, it is from this activity that students get closer to the professional reality. Due to the COVID-19 pandemic, there were several changes in higher education and also in the internship fields. Thus, the objective of this study is to report the experience of students of the bachelor's degree in psychology through the experiences of the supervised internship in health psychology during the pandemic of COVID-19. The supervised internship was carried out in the medical clinic of a private higher education institution, in the city of Belém do Pará during the month of July 2020, and had the supervision and planning of activities focusing on the selection of topics that address mental health. Thus, two actions were taken, the first was about self-care for mental health and the second was about changes in relationships caused by the pandemic context. Despite the limitations presented in this new internship context, the objective of this study was achieved, in which there must be adaptations by students and teachers. These factors, even challenging, were also conducive to learning new skills.